The Benefits of Climate Finance for Sustainable Livestock Systems in Low- and Middle-Income Countries - Cramer, Laura; Ngome, D.; Awolala, D.; Mbole-Kariuki, M.; Paul, B.; Wamukoya, G. (2025)
This policy note describes how global climate finance remains misaligned with the needs and potential of sustainable livestock systems in low- and middle-income countries (LMICs), despite their capacity to deliver the “triple wins” of climate mitigation, adaptation, and socio-economic development. It highlights how livestock systems contribute to food and nutrition security, soil health, ecosystem management, and rural livelihoods, yet receive minimal climate finance. The note calls for a reframing of livestock’s role within climate action and outlines policy measures for the G20 and development partners to mobilise greater investment into the sector. Key recommendations include developing blended finance instruments, scaling out carbon credit standards for rangelands and methane reductions, updating climate fund eligibility criteria, and creating climate-smart livestock indicators and monitoring and evaluation systems.